Financial frictions and foreign direct investment: Theory and evidence from Japanese microdata - Horst Raff; Michael Ryan; Frank Stähler (Kiel Institute for the World Economy (IfW), 2015)
We use Japanese microdata to examine how financial market frictions affect foreign direct investment (FDI). The Japanese land price bubble and banking trouble in the late 1980s and early 1990s serve as a quasi natural experiment to identify two possible transmission channels from financial shocks to FDI: (i) a collateral channel, whereby changes in the value of collateral affect investors' ability to borrow; and (ii) a lending channel, whereby changes in bank health affect banks' ability to lend. We find evidence that both transmission channels are statistically significant and economically important.
Keywords: F23; L20; 330; foreign direct investment; multinational enterprise; financing; credit rationing; collateral; bank health; Japan